Profil Kesiapan Mahasiswa dalam Memberikan Layanan Konseling Multikultural (Studi pada Mahasiswa BK Angkatan 2016 STKIP PGRI Sumatera Barat) - Zurika Marlinda, Sri (Lembaga Riset Mutiara Akbar, 2022)
This research is motivated by the existence of students who lack an understanding of cultural diversity, there are students who do not understand cultural knowledge, there are students who find it difficult to do counseling with clients of different cultures. The aim of this research is to describe the profile of students' readiness in providing multicultural counseling services. This research was conducted using a quantitative descriptive method. The research population is all active guidance and counseling students who have taken and passed cross-cultural counseling courses in 2016 STKIP PGRI West Sumatra. Based on the results of the research, the profile of student readiness in providing multicultural counseling services can be seen from: Cultural-historical is in the quite ready category with a percentage of 45.61%, psychosocial is in the quite ready category with a percentage of 33.33%, scientific-ideological is in the quite ready category with a percentage of 40.35%. The results of this study can be recommended so that students increase readiness in providing multicultural counseling services